OPTIMALISASI PENGAWASAN PENDISTRIBUSIAN LIQUEFIED PETROLEUM GAS TABUNG 3 KILOGRAM OLEH DINAS PERDAGANGAN KABUPATEN KUDUS - Raisa Rafifiti Choerunnisa; Ferlina Ardiyan (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
This research aims to analyze the supervision of the distribution of 3 kilogram LPG gas cylinders and to examine efforts to optimize the supervision of the distribution of 3 kilogram LPG gas cylinders in Kudus Regency. The method of this research is descriptive qualitative research. Data collection was conducted through interviews and document studies. This research was carried out based on the phenomenon occurring at the Department of Trade of Kudus Regency, particularly regarding issues such as differences in the retail ceiling price (HET) at various distribution bases, the presence of illegal distribution bases, and the misallocation of 3-kilogram LPG gas cylinders, which has led to gas shortages. The results of the study indicate that the supervision carried out by the Department of Trade has not been optimal due to several obstacles, including limited human resources, the absence of strict sanctions, lack of community participation, and suboptimal public outreach. The theoretical framework used in this study is the supervision theory proposed by Hani Handoko. Recommendations include increasing the number of staff to enable a structured schedule for monitoring the distribution of 3 kilogram LPG gas cylinders. Additionally, it is advised to disseminate information or install notices regarding sanctions for distribution bases that violate regulations. Public outreach activities should also be conducted periodically for agents, distribution bases, and the general public.